Kalimât al-Khamr fî al-Qur’ân: Dirâsat Tafsîriyat Lughawiyyat fî Ta’rîfihâ wa Tankîrihâ - Muhamad Rezi (Universitas Darussalam Gontor, 2021)
Quran, as the main source of Islam and the last revelation of Allah, contains countless knowledge and solutions of any creature’s problems. Quran explains most of matter with general terms and condition then Prophet Muhammad came with specific explanation. It signifies that any problem mentioned in Quran, whether generally or specifically, such a big problem of any creature. One of it is khamr. Khamr is an Arabic terms which is usually identified as intoxicating drinks or alcohol. Quran mentions word khamr in several verses in different Surah. It mentions with diverse word forms and patterns. Some of them are written in Arabic general form (nakirah) and others are in specific form (ma’rifah). Therefore, this diversity must create various meanings of the word. This paper aims to discuss the several of term khamr in Quran due to the distinct patterns of the words. It is focused on the Arabic linguistic study for issuing the basic meaning of khamr. Therefore, common people and moslem scholar may know what the true meaning of khamr. This research find that not all Khamr mentioned in pertain to unlawful thing, for only that which is written in specific form (ma’rifah) or with (ال) pertains to it.